The Calar Alto CAFOS direct imaging first data release. Issue 2 (14th March 2023) - Cortés-Contreras, M; Solano, E; Alonso-Hernández, J; Cardiel, N; Cruz, P; Rodrigo, C
ABSTRACT: We present the first release of the Calar Alto CAFOS direct imaging data, a project led by the Spanish Virtual Observatory with the goal of enhancing the use of the Calar Alto archive by the astrophysics community. Data Release 1 contains 23 903 reduced and astrometrically calibrated images taken from 2008 March to 2019 July with a median of the mean uncertainties in the astrometric calibration of 0.04 arcsec. The catalogue associated to 6132 images in the Sloan griz filters provides accurate astrometry and PSF calibrated photometry for 139 337 point-like detections corresponding to 21 985 different sources extracted from a selection of 2338 good-quality images. The mean internal astrometric and photometric accuracies are 0.05 arcsec and 0.04 mag, respectively. In this work we describe the approach followed to process and calibrate the images, and the construction of the associated catalogue, together with the validation quality tests carried out. Finally, we present three cases to prove the science capabilities of the catalogue: discovery and identification of asteroids, identification of potential transients, and identification of cool and ultracool dwarfs.